2022
DOI: 10.48550/arxiv.2203.10975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GCF: Generalized Causal Forest for Heterogeneous Treatment Effect Estimation in Online Marketplace

Abstract: Uplift modeling is a rapidly growing approach that utilizes machine learning and causal inference methods to estimate the heterogeneous treatment effects. It has been widely adopted and applied to online marketplaces to assist large-scale decision-making in recent years. The existing popular methods, like forest-based modeling, either work only for discrete treatments or make partially linear or parametric assumptions that may suffer from model misspecification. To alleviate these problems, we extend causal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Given the importance and unique challenges of uplift modeling, researchers in academia and industry have done extensive research in recent years. Uplift prediction models have evolved from metalearners-based [4,19,23], tree and forest-based [1,3,9,24,29,30], Knapsack problem-based [2,14] to deep neural networks-based architecture. Notably, many recent works have focused on developing new neural network architectures to better adapt to uplift modeling in industrial scenarios and shown remarkable performance improvements, such as EUEN [18], DESCN [34] and EFIN [21] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance and unique challenges of uplift modeling, researchers in academia and industry have done extensive research in recent years. Uplift prediction models have evolved from metalearners-based [4,19,23], tree and forest-based [1,3,9,24,29,30], Knapsack problem-based [2,14] to deep neural networks-based architecture. Notably, many recent works have focused on developing new neural network architectures to better adapt to uplift modeling in industrial scenarios and shown remarkable performance improvements, such as EUEN [18], DESCN [34] and EFIN [21] and so on.…”
Section: Introductionmentioning
confidence: 99%